Dose dependent effects of inhaled ethylene oxide on spermatogenesis in rats. Issue 4 (April 1991) - Mori, K; Kaido, M; Fujishiro, K; Inoue, N; Koide, O; Hori, H; Tanaka, I
Abstract : Male Wistar rats were exposed to ethylene oxide (EO) at concentrations of 50, 100, or 250 ppm for six hours a day, on five days a week for 13 weeks. Dose effect relations of inhaled EO on spermatogenesis were evaluated from testicular and epididymal weights, histopathological changes and lactate dehydrogenase X (LDH X) activity in the testis, and sperm counts and sperm head abnormalities in the epididymis. At 250 ppm, a decrease in epididymal weights, slight degenerations in the seminiferous tubules, decreased sperm counts, and increased numbers of abnormal sperm heads in the tail of the epididymis were found; these were not seen at lower doses. When the abnormal sperm heads were classified into immature types and teratic types, the number of immature heads increased only at 250 ppm. On the other hand, the teratic type had increased at doses of 50 and 100 ppm EO when compared with the control group. Hence, subchronic inhalation of EO at low concentrations affects spermatogenesis in rats.